2010
DOI: 10.1142/s0219581x10006491
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Behavior of a Twisted Carbon Nanotube Yarn

Abstract: Carbon nanotube (CNT) yarns were drawn from the web found on the CVD furnace wall. The yarns were twisted and their tensile behavior was investigated through in-situ SEM and regular tensile tests. The mechanisms involved in the CNT yarn deformation were identified. The twisted CNT yarns were found to have a good ability to stretch and deform and featured a diameter-dependent strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 8 publications
4
84
1
Order By: Relevance
“…5a). Figure 5b reflects the bundle-forming tendency of f-MWCNTs; a similar morphology is reported earlier by Allaoui et al 18 The compositional mapping with AFM is often used for the identification of multiple phases through color contrast. The brighter areas in the image can be attributed to the greater force experienced by the cantilever tip when in contact with the filler (tubular or spherical), whereas dark patches appear when the tip is in contact with the amorphous matrix state.…”
Section: Structural Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…5a). Figure 5b reflects the bundle-forming tendency of f-MWCNTs; a similar morphology is reported earlier by Allaoui et al 18 The compositional mapping with AFM is often used for the identification of multiple phases through color contrast. The brighter areas in the image can be attributed to the greater force experienced by the cantilever tip when in contact with the filler (tubular or spherical), whereas dark patches appear when the tip is in contact with the amorphous matrix state.…”
Section: Structural Analysissupporting
confidence: 78%
“…The strong interaction between the multiwalled carbon nanotube (MWCNT) and biphenyl liquid crystalline epoxy composites exhibits excellent thermal and mechanical properties. 17 Allaoui et al 18 investigated the effect of MWCNT on a rubbery epoxy matrix and found that the addition of 4 wt% MWCNT led to a significant increase in the strength and Young's modulus. Montazeri et al 19 reported that epoxy with 0.5 wt% MWCNT showed better tensile strength and Young's modulus as compared to epoxy.…”
mentioning
confidence: 99%
“…A review of existing literature on the mechanical properties of CNT reinforced polymer composites demonstrates that many studies have been done recently e.g., [1][2][3][4][5][6][7][8][9][10][11] . Significant improvements in mechanical properties of polymeric matrixes have been reported by adding a few weight-percents (wt%) of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5]7,11,[13][14][15][16][17][18]12,20,21,25,[35][36][37][38][39][40][41][42][43][44][45][46] However, the cost comparison with cheaper reinforcement particulates does not proportionately favor the use of nanotubes.…”
Section: Introductionmentioning
confidence: 99%